Spontaneous perforation of caecum, a rare entity: case report and review of literature - Sharma, Rakesh; Padhy, Biren P.; Kumar, Supreet; Suchithra, G. Lakshmi; Hareesh, Meka (International Surgery Journal, 2018)
Spontaneous perforation of caecum is a rare entity. Here we present a case of 72-year-old male who had presented with pain, distension of abdomen with tense pneumo-peritonium and peritonitis. Exploratory laparotomy showed caecal perforation without any obvious cause. Various theories have been proposed regarding the pathology but still its etiology remains a dilemma. Though it is not a common entity, it weighs a high importance in case of diagnosis and prompt intervention due to its high mortality from peritonitis and septicaemia.